Impacts of Working Capital Management on Profitability: A Comparative Study on Cement and Tannery Industry of Bangladesh - Syed Md. Rahman; Salman Ahmed (International Journal of Management, Accounting and Economics, 2021)
Short term asset and liability management is significant in corporate finance literature. This paper investigated on the impacts of working capital management (WCM) on profitability of listed companies of cement and tannery industry in Bangladesh. The data of companies has been collected from Dhaka Stock Exchange over the period 2008-2017. Five firms were chosen from each industry by applying simple random sampling method. Study found that WCM has significant impact on profitability. Result revealed that if average payment period, and cash conversion cycle increase it leads to decrease in all four profitability ratios of cement industry’s firms. Cash conversion cycle has significant negative impact on ROE while current ratio (CR) has significant positive effect on NPM. In contrast, tannery industry impacted by days sales outstanding (DSO) negatively. More inventory turnover has reduced ROE & ROCE while stretching payables reduced ROA & NPM. DSO has significant negative and CR has significant positive impact on NPM of tannery industry’s firms. The managers can increase their companies’ profitability by reducing the days sales outstanding, days inventory turnover, cash conversion cycle and average payment period. The study has practical and policy implications for corporate managers, suppliers, customers, and competitors as enhanced profitability has direct and indirect effect on all stakeholders.